2022
DOI: 10.3390/ma15207296
|View full text |Cite
|
Sign up to set email alerts
|

Irradiation Damage Independent Deuterium Retention in WMoTaNbV

Abstract: High entropy alloys are a promising new class of metal alloys with outstanding radiation resistance and thermal stability. The interaction with hydrogen might, however, have desired (H storage) or undesired effects, such as hydrogen-induced embrittlement or tritium retention in the fusion reactor wall. High entropy alloy WMoTaNbV and bulk W samples were used to study the quantity of irradiation-induced trapping sites and properties of D retention by employing thermal desorption spectrometry, secondary ion mass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The above mechanisms prevent hydrogen concentrations from reaching the highest possible ratios at room temperature, but also help retain much of the hydrogen once it is absorbed, as found in Ref. [ 18 ]. The limited diffusion due to local strains and chemical diversity may add to the energy barrier created by a primary trap, making its de-trapping energy higher.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…The above mechanisms prevent hydrogen concentrations from reaching the highest possible ratios at room temperature, but also help retain much of the hydrogen once it is absorbed, as found in Ref. [ 18 ]. The limited diffusion due to local strains and chemical diversity may add to the energy barrier created by a primary trap, making its de-trapping energy higher.…”
Section: Discussionmentioning
confidence: 88%
“…The prospective for industrial applications of high-entropy alloys underline the importance of gaining qualitative knowledge about the processes influencing the absorption of hydrogen. In previous research, a number of V-rich HEAs have been observed to absorb hydrogen, this includes the WMoTaNbV alloy studied in this work [ 17 , 18 ]. The WMoTaNbV efficiently traps hydrogen, with an energy of ∼1.7 eV [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation